THE STUDENTS’ ABILITY IN FULL TRANSLATION OF THE HARRY POTTER STORY TEXT - ADE ROSA ARIANTI NASUTION (JURNAL ILMIAH MAKSITEK, 2022)
This thesis carried out to describe the students ability in Full Translation of Harry Potter Story Text. Therefore, classroom research was carried out the finding and the writer choosed sixth semester academic year 2021/2022 of English Department Muhammadiyah University of North Sumatera. Jl. Kapt. Muchtar Basri No. 3. The population consisted of sixth classes was take as the sample randomly. A set of translation test, which consist of 10 sentences were administrated to collect the data, and the analysis based on quantitative descriptive. The result of the research showed that generally 93.88 % or 46 students from the whole sample who were able to translate Harry Potter Story text into Indonesia correctly, whereas there are 3 students or 6.12 % from the whole sample who were unable. It means that the 2021/2022 sixth semester were able to translate Harry Potter Story text by using full translation procedures.